The Study of Seaweed Cultivation Development in Bone District - Mustafa Mustafa; Toto Hardianto; Yakub Suleman; Feby Triadi (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2022)
Some cultivators depend on the owners of capital, such as traders and entrepreneurs, so there is dependence on the owners of the capital. This study aims to determine the main factors that influence the development of seaweed cultivation; measure the contribution of these main factors to the development of seaweed cultivation, and determine the strategy for developing seaweed cultivation in Tanete Riattang District. East. Data were collected using observation, interview, and participatory rapid appraisal methods. Data were analyzed qualitatively. The results show that the main factors that influence the development of seaweed cultivation are the availability of 85.9% land with decent conditions, labor, business feasibility of 1.34 based on OI/Ratio analysis, access to capital, marketing results, post-harvest handling, and local government policies. Together and integrated, the main factors contribute to supporting and hindering the development of seaweed aquaculture. Possible development strategies These are land management and construction design of cultivation methods, application of long line and floating raft methods in offshore waters, activating extension of the